Performance of self-collected saliva samples for SARS-CoV-2 mass testing in community settings - Olivia Kay; Matthias E Futschik; Elena Turek; David Chapman; Simon Carr; Malur Sudhanva; Paul E. Klapper; Tony Cox; Michael Hill; Joanna Cole-Hamilton; Peter Marks; Sarah A Tunkel; et al. (Journal of Clinical Virology Plus, 2023)
Background: Saliva has been considered a suitable sample material for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNA testing, but uncertainty remained regarding sensitivity and reliability of different saliva collection methods. Objectives: This study aimed to investigate the potential utility of expectorated saliva (ES) and drooled saliva (DS) for community mass testing. Study design: Self-collected ES and DS samples were obtained in a prospective cohort study with 2,878 participants. The utility of saliva for SARS-CoV-2 qRT-PCR testing was assessed by comparing the capacity to detect SARS-CoV-2 positive cases with results for self-collected combined throat and nose (CTN) swabs. Additionally, quantification cycle (Cq) values were compared. Results: ES- and DS-based tests showed the same high level of concordance (98% vs 98%) with CTN swab-based results. Sensitivity was higher for DS (94%) than for ES (83%) or CTN swab (90%) but differences were statistically not significant. Comparing only symptomatic cases, however, a significantly higher sensitivity of DS (96%) than of ES (76%) or CTN swab (91%) was observed. Cq values of saliva and swab specimen were significantly correlated and appeared to be not impacted by age or other potentially confounding factors. Conclusions: Saliva-based SARS-CoV-2 RNA testing showed high diagnostic accuracy and can be considered an alternative where swabbing may not be tolerated or operationally feasible. DS yielded the same or better diagnostic performance compared to ES and may present a preferred option with reduced aerosol risk and increased compliance.